Siouan Languages and Linguistics : Selected Papers - Rood, David,; Boyle, John, (Brill's Studies in Language, Cognition and Culture ;, 2019)
Robert L. Rankin was a seminal figure in late 20th and early 21st centuries in the field of Siouan linguistics. His knowledge, like the papers he produced, was voluminous. We have gathered here a representation of his work that spans over thirty years. The papers presented here focus on both the languages Rankin studied in depth (Quapaw, Kansa, Biloxi, Ofo, and Tutelo) and comparative historical work on the Siouan language family in general. While many of the papers included have been previously published, one third of them have never before been made public including a grammatical sketch and dictionary of Ofo and his final paper on the place of Mandan in the larger Siouan family.